Transition metal-free [2,3]-sigmatropic rearrangement in the reaction of sulfur ylides with allenoates - García-Castro, Miguel; Moya-Utrera, Federico; Sarabia-García, Francisco Ramón (RSC, 2023)
An unprecedented transition metal free [2,3]-sigmatropic rearrangement involving stabilized sulfur ylides and allenoates has been thoroughly established. The scope and utility of this reaction have been extensively studied resulting in C–C bond formation under mild conditions with greater than 20 examples reported. A highlight of the work is the simple and fully operational process that does not involve the use of carbenes or the associated hazardous and sensitive reagents. The reaction can be performed at room temperature and using an open flask. Interestingly, the new C–C bond formation reaction is gram scalable, and the obtained isomers are readily separable, affording interesting building blocks that can be used in the preparation of complex molecules.
Keywords: Química orgánica; Reacciones químicas; Reactividad (Química); Reacciones químicas orgánicas - Mecanismos; Sigmatropic rearrangement; Sulfur ylides; Allenoates; Carbon-carbon bond; Complex molecules